Experimental Investigation and Performance Analysis on R134a Air Source Heat Pump Water Heater - Wang Zhihua; Zheng Yuxin; Hao Jibo; Li Jingchao; Wang Fenghao (Zhileng xuebao)
Experiments of an air source heat pump water heater(ASHPWH) using R134a prototype were carried out and analyzed the effects of improper refrigerant charge and incorrect TXV opening on the system. The performance of the system were measured in combinations of four refrigerant charges of 70%，85%，100% and 115% of the optimal value and three TXV opening of 30%, 45% and 60% of full opening at ambient temperature of 20/15℃. The results showed that the system COP was increased to a point and then tended to decrease, the expansion valve opening had a significant impact on performance, it was found that increasing the TXV opening can enhance COP when water temperature above 32°C. Based on the experimental investigations, an exergy analysis was conducted to evaluate the thermodynamic performance of the system and components in this study. It was found that exergy losing of the system was mainly occurred in the compressor and condenser. The system exergy efficiency was decreased with water temperature increased, it was decreased by 8% and 10% respectively when the expansion valve opening was 30% and 60%.